Maternal body mass index and country of birth in relation to the adverse outcomes of large for gestational age and gestational diabetes mellitus in a retrospective cohort of Australian pregnant women - Catherine R. Knight-Agarwal; Rati Jani; Meisa Al Foraih; Dionne Eckley; Carrie Ka Wai Lui; Shawn Somerset; Deborah Davis; Monica Yuri Takito (BMC, 2021)
Abstract Background The prevalence of gestational diabetes mellitus in Australia has been rising in line with the increased incidence of maternal overweight and obesity. Women with gestational diabetes mellitus, high body mass index or both are at an elevated risk of birthing a large for gestational age infant. The aim was to explore the relationship between country of birth, maternal body mass index with large for gestational age, and gestational diabetes mellitus. In addition to provide additional information for clinicians when making a risk assessment for large for gestational age babies. Method A retrospective cohort study of 27,814 women residing in Australia but born in other countries, who gave birth to a singleton infant between 2008 and 2017 was undertaken. Logistic regression analysis was used to examine the association between the aforementioned variables. Results A significantly higher proportion of large for gestational age infants was born to overweight and obese women compared to those who were classified as underweight and healthy weight. Asian-born women residing in Australia, with a body mass index of ≥40 kg/m2, had an adjusted odds ratio of 9.926 (3.859-25.535) for birthing a large for gestational age infant. Conversely, Australian-born women with a body mass index of ≥40 kg/m2 had an adjusted odds ratio of 2.661 (2.256-3.139) for the same outcome. Women born in Australia were at high risk of birthing a large for gestational age infant in the presence of insulin-requiring gestational diabetes mellitus, but this risk was not significant for those with the diet-controlled type. Asian-born women did not present an elevated risk of birthing a large for gestational age infant, in either the diet controlled, or insulin requiring gestational diabetes mellitus groups. Conclusions Women who are overweight or obese, and considering a pregnancy, are encouraged to seek culturally appropriate nutrition and weight management advice during the periconception period to reduce their risk of adverse outcomes.